Detection and characterization of monoclonal antibodies to platelet membrane proteins (The Rockefeller University Press, 1981)
We have devised a solid-phase radioimmunoassay for the detection and characterization of monoclonal antibodies directed against platelet surface antigens. Platelet membrane proteins, solubilized with 0.1% Triton X-100, were covalently coupled to cyanogen bromide (CNBr)- activated filter paper disks that were than used as the support in antibody binding assays. SDS PAGE of solubilized membrane proteins taken immediately before and after incubation with activated disks indicated that representative amounts of each membrane protein were bound to the disks. Either monoclonal or heterologous anti-platelet antibody could be detected on disks that had been prepared using as little as 50 micrograms of membrane protein per 100 disks. For the detection of antibody, disks were incubated with test sera for 2 h, washed, and incubated with 125I-labeled anti-immunoglobulin G, and the amount of bound radioactivity was determined. The sensitivity of the disk assay in detecting monoclonal antibodies was far greater than that of a corresponding radioimmunoassay that used whole platelets as the solid phase. By linking other proteins such as fibrinogen or anti-mouse subclass specific antisera to CNBr-activated disks, the method was adapted for antibody characterization. The sensitivity and ease with which the assay can be performed make this technique most suitable for screening and characterizing monoclonal antibodies.